Evaluation of the Nutrient Composition of Maize in Different NPK Fertilizer Levels Based on Multivariate Method Analysis - Csaba Bojtor; Árpád Illés; Seyed Mohammad Nasir Mousavi; Adrienn Széles; Brigitta Tóth; János Nagy; Csaba L. Marton (International Journal of Agronomy)
One of the critical issues in using micronutrient fertilisers is the comparison of methods and amounts of fertiliser use, which is very important from the aspect of increasing production and economic viewpoint. The aim of this research was to analyse the nutrient composition of different parts of the maize (Zea mays L. FAO 490) during the growing season with six-level nitrogen fertilisation supplies at five phenological stages. The study included essential nutrients as nitrogen (N), phosphorus (P), potassium (K), and sulphur (S) (in first cluster) and calcium (Ca) and magnesium (Mg) (in second cluster) in treatments on different leaf stage. Growth stages have different nutrient demands based on their actual demand. The first cluster included nitrogen and sulphur and the second included calcium and zinc in the NPK treatments on the stalk of plants. Nitrogen and potassium had their maximum effect on the stalk of maize during the growing season. Magnesium and copper were the second most important and desirable factors during the different growth stages and treatments in relation to the stalk. Nitrogen and calcium had their maximum impact during the yield formation stage and nitrogen and phosphorus had their most desirable effect during the grain filling stage. The effect of nitrogen on the quantitative and qualitative properties of maize showed that nitrogen increases the production of dry matter, grain yield, and its components. The maximum amount of absorption in the plants occurs before the accumulation of applied fertiliser, which is the prelude to the production of maximum biomass.